ANALISA MANFAAT EKONOMI DAN PERAN LEMBAGA PETANI TAMBAK (Studi Deskriptif di Desa Ambeng-ambeng Watang rejo Kecamatan Duduk Sampeyan Kabupaten Gresik) - Winarto; M. Husni Tamrin (Faculty of Social and Political Science, 2017)
Fishery aquaculture activities become the core livelihood in some communities in rural areas. This study describes the value of economic benefits and the role of pond farming institutions in the community that became the needs and daily livelihoods. This research observes how the value of economic benefits and how the role of pond farming institutions in the Village of Ambeng-ambeng Watangrejo Duduk Sampeyan District Gresik.The results of this study conclude that the economic benefit value for the farmers is not profitable and even a loss. The role of farmer groups that have not yet had a good function. Group